(3JfejI GdegGQGJ GdEOGQjI (B/s - (3WjHj, QJjHIs ((3YeGf(B: s (3OGQ GdGYUGQ GdYdej ddfTQ hGdJhRjY(B, s, 2016)
(3CKQ GdJOQjH aj QaY caGAI COGA GdYGedjf,GdegGQGJ GdbjGOjI,aQjb GdYed GdaYGd,GdEOGQI hGdeOjQ,EYOGO hcJGHI GdQSGFd hGdJbGQjQ,OhQ GdJCgjd hGdJOQjH Gdegfj aj JfejI GdegGQGJ GdHTQjIs
(3HHdjhZQGajG(B:(3U(B.319-324s
Keywords: (3GdGOGQIs; (3GdJfejI GdGOGQjIs